If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -4j + 5(-4j + 6) = -42 Reorder the terms: -4j + 5(6 + -4j) = -42 -4j + (6 * 5 + -4j * 5) = -42 -4j + (30 + -20j) = -42 Reorder the terms: 30 + -4j + -20j = -42 Combine like terms: -4j + -20j = -24j 30 + -24j = -42 Solving 30 + -24j = -42 Solving for variable 'j'. Move all terms containing j to the left, all other terms to the right. Add '-30' to each side of the equation. 30 + -30 + -24j = -42 + -30 Combine like terms: 30 + -30 = 0 0 + -24j = -42 + -30 -24j = -42 + -30 Combine like terms: -42 + -30 = -72 -24j = -72 Divide each side by '-24'. j = 3 Simplifying j = 3
| Y+5=2(x-2) | | (m-2)/3=-1 | | -24+8x=-24-40x | | 3=24x | | Y-2=2(x+2) | | -9=.29n | | 3x+4x+8x=180 | | -34+7v=-5(-4+4v) | | 2x-83=17 | | (5x^3+7x^2-x-3)/(x+1) | | (3x-1)/(x-5) | | Y+1=3(x-2) | | N^2+13n+40/8n | | (8/X)=-18 | | 3x-1/x-5 | | 4x-32=3x+11 | | 4x-2(3x+17)=-54 | | 5d+9=4 | | 5x-13+90=16x-55 | | x/4-9=5 | | Y+2=3(x+4) | | 0.113x=95.46-x | | 3t^6-49t^2=0 | | 20+6x=4x+14 | | 24x^2-28x-12=0 | | m^3-4m^2+6m-24=0 | | 7x-8(x+4)=2 | | 7.2s-19.6s-16.87=-10.9s-3.82 | | ln(x-6)+ln(x-5)=ln(16-2x) | | Y-4=2(x+3) | | 1+x=3x+29 | | -4.2c+13.8=-12.8-6.1c |